THE LINGUISTIC PORTRAIT OF A CHARACTER AS AN OBJECT OF LINGUOPERSONOLOGY (Multidisciplinary Journal of Science and Technology, 2024)
this article gives information about linguistic portrait of a character in linguopersonology as well as provide several feasible notions namely three primary avenues for language acquisition and description of the character